"Smooth operator": Music modulates the perceived creaminess, sweetness, and bitterness of chocolate. (1st January 2017) - Reinoso Carvalho, Felipe; Wang, Qian (Janice); van Ee, Raymond; Persoone, Dominique; Spence, Charles
Abstract: There has been a recent growth of interest in determining whether sound (specifically music and soundscapes) can enhance not only the basic taste attributes associated with food and beverage items (such as sweetness, bitterness, sourness, etc.), but also other important components of the tasting experience, such as, for instance, crunchiness, creaminess, and/or carbonation. In the present study, participants evaluated the perceived creaminess of chocolate. Two contrasting soundtracks were produced with such texture-correspondences in mind, and validated by means of a pre-test. The participants tasted the same chocolate twice (without knowing that the chocolates were identical), each time listening to one of the soundtracks. The 'creamy' soundtrack enhanced the perceived creaminess and sweetness of the chocolates, as compared to the ratings given while listening to the 'rough' soundtrack. Moreover, while the participants preferred the creamy soundtrack, this difference did not appear to affect their overall enjoyment of the chocolates. Interestingly, and in contrast with previous similar studies, these results demonstrate that in certain cases, sounds can have a perceptual effect on gustatory food attributes without necessarily altering the hedonic experience.